O aspecto da racionalidade na economia institucional: uma análise comparativa entre a antiga economia institucional de Thorstein Veblen e a nova economia institucional de Douglass North - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The resumption of the discussion about institutions in the economy in the mid-1960s shows the need to use theories and methods of economic analysis that encompasses the nuances of economic reality that neoclassical reductionist models did not contemplate. The institutional economy originated in the United States in the late nineteenth century with the works of Thorstein Veblen. With its discontent with the theoretical models that dominated the mainstream of economics, the author proposes an approach that understands history, which disregards methodological individualism and inserts an understanding of the role of institutions in economics. The study of institutions in the economy by the so-called New Institutional Economy has a proposal different from the one initiated by Veblen. Douglass North is one of the authors who inserts into this field of research. Despite the criticism of this author, he aims to broaden the scope of neoclassical research through the analysis of institutions and not to propose a theory to replace it. North also disregards the rationality assumption used by economic orthodoxy, and argues that limited rationality is one of the reasons for the existence of institutions. This study aims to demonstrate and evaluate the aspects of the understanding of rationality adopted by Veblen and North. Moreover, with that to compare their fundamental differences and what that implies in the theoretical approach of each author. For that, we used the comparative analytical method based on the works of the authors and other authors who wrote about the subject. It was concluded that the two aspects show similarities as the consideration of historical aspects of economic phenomena, overcoming the presupposition of unlimited rationality and symmetrical information of neoclassical theory, and of course the importance of institutions. However, it must be acknowledged that the proposals are quite distinct, what Veblen proposes is a multidisciplinary "evolutionary" economic theory as an influence of biology, psychology, and sociology. What North proposes is a revision of the neoclassical economic apparatus, although it considers the history and progress in the use of cognitive theories to interpret the human actions.
Keywords: Economia institucional; Racionalidade; Thorstein veblen; Douglass North; Institutional economy; Racionality; Thorstein veblen; CNPQ::CIENCIAS SOCIAIS APLICADAS